Upper gastrointestinal bleeding due to tuberculous mesenteric lymphadenitis that fistulizes the gastric wall - Ramírez Garcia, Juan Felipe (2021)
Tuberculous lymphadenitis is the most common entity of abdominal tuberculosis, which occurs due to reactivation of a latent focus. Its diagnosis requires a high degree of suspicion, for which it requires endoscopic, radiological, and histopathological studies. In the evaluation of lymphadenopathies, endoscopic ultrasound-guided aspiration puncture plays an important role. We present the case of a 22-year-old male patient who was admitted to the Emergency Department of the Arzobispo Loayza National Hospital due to upper gastrointestinal bleeding secondary to tuberculous mesenteric lymphadenitis that compromised the gastric wall.